Cardiometabolic Profile Screening as an Early Detection of Cardiometabolic Risk - Sarastri, Yuke; Raynaldo, Abdul Halim; Ilyas, Kamal Kharrazi; lubis, Dian Anindita (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background: Cardiometabolic risk profile is a set of interconnected risk factors, namely abdominal obesity, hypertension, dyslipidemia, hyperglycemia, and hyperinsulinemia, and causes global death. This study was conducted to obtain data on cardiometabolic profiles of people who participated in the Commemoration of World Hypertension Day 2021 at RSUP H Adam Malik Medan Method: This research is a descriptive study with a cross-sectional research design peoples namely by looking at the description of the cardiometabolic profile. The sample is an affordable population that meets the inclusion criteria, people with age >18 years old. Variables of blood pressure, waist circumference, blood sugar levels, and total cholesterol levels are numerical variables. Blood pressure examination is measured using a sphygmomanometer and expressed in mmHg units. The measurement of the abdominal circumference is carried out by examining the size of the abdominal circumference obtained using a tape measure in cm. Blood sugar levels are obtained from the results of measuring blood sugar levels during laboratory examination of blood in mg/dl units. Cholesterol levels are obtained from the results of measuring total cholesterol levels from blood laboratory examinations in mg/dl.  Results: All subjects in this study (n= 100) are 42 men and 58 women with normal waist circumference, and education level strata -1, only 9% of the subjects had high blood sugar levels, and 41% of subjects were classified as central obesity 9% of subjects. Most patients (91%) with normal postprandial glucose and high total cholesterol 66%. Conclusion: In this study, most of the cardiometabolic risks of patients are overweight/obesity and dyslipidemia